Management of Asrigdara in women of Late Reproductive Age Group w.s.r. to AUB: An Open-Label, Randomized, and Parallel Clinical Study - Gaiju, Laxmita; Shukla, Seema (International Research Journal of Ayurveda & Yoga, 2025)
Background: In recent times, menstrual and hormonal irregularities have become more common in women of all ages. Menstrual conditions with bleeding more than normal, for prolonged period, or irregular bleeding are included in Abnormal Uterine Bleeding (AUB). Management in conventional science for the same includes of hormonal management or invasive surgeries which have their own drawbacks. Opting for safer alternative like Ayurveda shows great benefits in the management of AUB. Objective: The objective of this study was to assess efficacy of Ayurvedic interventions; “Madhukadi Yoga” and “Madhukadi Tailam Matra Vasti” in the management of AUB (Asrigdara). Materials and Methods: An open-label, interventional, and parallel study with 30 participants was conducted and they were randomly divided into two groups. One of which was given Madhukadi Yoga orally and Madhukadi Tailam Matra Basti, whereas the other group was administered with only oral drug for three consecutive cycles. Evaluation was made on the basis of subjective and objective assessment criteria by applying paired T test before and after completion of the intervention and comparison was made between both groups using statistical tests. Results: Comparatively better results were obtained among patients receiving both the Madhukadi Yoga orally and Madhukadi Tailam Matra Basti than the other group. Conclusion: The findings offer preliminary evidence of the safety and possible advantages of Ayurveda in the treatment of AUB. To suggest the use of these therapies in ordinary clinical practice, more research with larger sample size should be conducted to produce strong proof of their therapeutic potential.